A review on strategies for decreasing E. coli O157:H7 risk in animals. (February 2017) - Saeedi, Pardis; Yazdanparast, Maryam; Behzadi, Elham; Salmanian, Ali Hatef; Mousavi, Seyed Latif; Nazarian, Shahram; Amani, Jafar
Abstract: Enterohemorrhagic Escherichia coli (EHEC) serotype O157:H7 is a food-borne pathogen that younger children are most prone to this microorganism. Hemolytic Uremic Syndrome (HUS) caused by EHEC, leads to the destruction of red blood cells and kidney failure. The virulence of E.coli O157:H7 is attributed to fimbriae, that facilitate colonization of bacteria within the colon and verotoxins (VT) or Shiga toxins (Stx) that are released into the blood. Although, in most cases, the infection is self-limitedin young children and aged population, it may cause HUS. Therefore, several investigations are performed in order to offer effective therapies and vaccines, which can prevent and treat the infection in appropriate time. As the pathogenesis of this infection is complicated, a multi-targeted strategy is required. Since cattle are the most important reservoir of EHEC and the root of contamination, reducing E. coli O157:H7 at the farm level should decrease the risk of human illness. Several vaccine approaches have been employed with different proper outcomes in animal models, including recombinant proteins (virulence factors such as; Stx1/2, intimin, EspA, fusion proteins of A and B Stx subunits), avirulent ghost cells of EHEC O157:H7, live attenuated bacteria expressing recombinant proteins, recombinant fimbrial proteins. In addition to protein-based vaccines, DNA vaccines have provided proper prevention in the laboratory animal model. This review paper summarizes the previous studies, current status and future perspective of different immunization strategies for eradicating Enterohemorrhagic Escherichia coli O157:H7. Highlights: Hemolytic Uremic Syndrome (HUS) caused by EHEC. Several vaccine approaches have been employed in animal models. The paper reviewed different vaccination studies.